AB1159 High dose glucocorticoids as a risk factor of sigmoid diverticulitis perforations in autoimmune diseases. (15th June 2017) - Kuranobu, T; Ishitoku, M; Tokunaga, T; Yoshida, Y; Hirata, S; Nojima, T; Sugiyama, E
Abstract : Background: It has been reported that glucocorticoids (GCs) and non-steroidal anti-inflammatory drugs (NSAIDs) might increase sigmoid diverticulitis perforations (SDPs) for rheumatoid arthritis patients, however, there are few previous reports referring to the relationship between SDPs and GCs in patients with systemic autoimmune diseases. We investigate relationship between SDPs and GCs in patients used GCs for not only rheumatic patients but also other autoimmune disease' sufferer. SDPs and GCs Objectives: To describe development of SDPs during high dose GC (over PSL 0.8mg/kg equivalent) therapy for systemic autoimmune diseases in our department, additionally reviewing previous reports with regard to the relationship between SDPs and GCs. Methods: 187 patients hospitalized in our department from April 2015 to December 2016 were retrospectively reviewed. Results: Among 187 patients, 61 took high dose GCs, 29 took moderate dose GCs (0.5–0.6mg/kg PSL equivalent), 53 took low dose (less than 0.5mg/kg PSL equivalent), and 29 didn't take GCs. Four patients out of 61 who took high dose GCs developed SDPs (table). Nobody developed SDPs in moderate, low and not any dose GCs group. Case 1–3 took NSAIDs. Case 2 received mPSL pulse therapy (mPSL 1 g x 3 days). Case 1 and 2 developed SDPs within 3 months from initiating GCs. Case 1 recurred SDPs at 17 and 63 months from initiating GCs. Case 2 was prescribed Tacrolimus as a concurrent medication. All four patients were operated to remove the perforated segment, and case 2 and 4 were created artificial anus. Although they were clinically diagnosed as SDPs only case 4 clarified perforation in pathological findings. Conclusions: We should take care of developing SDPs in patients described high dose GCs. References: Mpofu S, Mpofu CM, Hutchinson D, Maier AE, Dodd SR, Moots RJ. Steroids, non-steroidal anti-inflammatory drugs, and sigmoid diverticular abscess perforation in rheu- matic conditions. Ann Rheum Dis 2004; 63: 588–590. Humes DJ, Fleming KM, Spiller RC, West J. Concurrent drug use and the risk of perforated colonic diverticular dis- ease: a population-based case-control study. Gut 2011; 60: 219–224. Disclosure of Interest: None declared